The Role of Bisphosphonates in Preventing Fragility Fractures: A 10-Year Follow-Up Study - Das, Samyabrata; Samria, Kartik; E. A, Hizam Naseef (Journal of Neonatal Surgery, 2025)
Bisphosphonates serve as a pharmaceutical treatment to stop fractures among people who have osteoporosis which shows itself through reduced bone mineral density and elevated susceptibility to bone-breaking fractures. The purpose of this research is to determine how well bisphosphonates prevent fragility fractures during a 10-year observation period. The analysis included data about fracture occurrences and BMD changes and bisphosphonate safety measurements with special attention given to rare side effects such as osteonecrosis of the jaw (ONJ) and atypical femoral fractures. A research sample included people who were 50 years old or older with osteoporosis or those who had a high risk of bone fractures. The bisphosphonate treatment group achieved statistically lower rates of both vertebral and hip fractures compared to the control group. The treatment led to higher bone mineral density levels at the hip region and at the lumbar spine. The research demonstrated that bisphosphonate therapy extends risks through the development of osteonecrosis of the jaw (ONJ) and atypical femoral fractures. The research highlights the necessity for individualized therapy plans and additional studies about the best duration of treatment together with drug breaks and long-term treatment consequences.